Shoulder muscle activation during aquatic and dry land exercises in nonimpaired subjects - Kelly, B. T.; Roskin, L. A.; Kirkendall, D. T.; Speer, K. P. (Journal of Orthopaedic & Sports Physical Therapy, 2000)
Abstract: Study Design: Randomized, single blind experimental design using electromyography to measure shoulder muscle activation in nonimpaired subjects. Objectives: To compare the muscle activation of rotator cuff and shoulder synergists during rehabilitation exercises performed in water or on dry land. Background: Early motion is critical to restoration of normal shoulder function. Aquatic therapy has been promoted as a method for increasing range of motion while minimizing stress on the shoulder. Methods and Measures: The integrated electromyography amplitude of 6 muscles of the shoulder girdle was examined on the nondominant shoulders of 6 subjects (supraspinatus, infraspinatus, and subscapularis, anterior, middle, and posterior deltoids). Each subject performed elevation (0° to 90°) in the scapular plane with neutral rotation on land and in water at 3 different speeds of elevation (30°/s, 45°/s, and 90°/s). The mean percentage of the maximal voluntary contraction was determined for each of the 3 test speeds on land and in water. Comparisons between water and dry land were made with a repeated measures analysis of variance. Results: For all 6 muscles tested, muscle activation during the 30°/s test speed and all muscles tested at the 45°/s test speed was significantly less when performed in water versus when performed on land. For example, electromyography activation of the supraspinatus muscle was 16.68% of a maximal voluntary contraction when elevation at was performed at 30°/s on dry land versus 3.93% when performed in water. Conclusion: These data suggest that shoulder elevation in the water at slower speeds resulted in a significantly lower activation of the rotator cuff and synergistic muscles. This decreased muscle activation during aquatic physical therapy allows for earlier active motion in the postoperative period without compromising patient safety.